2018
DOI: 10.1002/dep2.51
|View full text |Cite
|
Sign up to set email alerts
|

In situ geochemistry of middle Ordovician dolomites of the upper Mississippi valley

Abstract: The dolomitization and diagenetic history of Ordovician carbonates of southern Wisconsin is complex. Previous studies attributed dolomitization to various diagenetic factors and environments. In this study, high‐resolution, in situ laser ablation inductively coupled mass spectrometry analysis of rare earth element patterns of dolomite was used to assess the diagenetic fluids responsible for dolomitization of the Ordovician Decorah Formation. Integrated geochemical data and petrographic evidence suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Petrographic and stratigraphic analyses have ruled out other potential sources of Mg for burrow dolomitization, such as surrounding evaporites (Zenger, 1996a), volcanic ash (Callen & Herrmann, 2019) and clay minerals (Chatalov, 2018), all of which are conspicuously absent from the Rumaila Formation and surrounding strata. Therefore, echinoderm fragments initially composed of HMC are the sole candidate for a potential Mg source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petrographic and stratigraphic analyses have ruled out other potential sources of Mg for burrow dolomitization, such as surrounding evaporites (Zenger, 1996a), volcanic ash (Callen & Herrmann, 2019) and clay minerals (Chatalov, 2018), all of which are conspicuously absent from the Rumaila Formation and surrounding strata. Therefore, echinoderm fragments initially composed of HMC are the sole candidate for a potential Mg source.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent source is dense saltwater with a high Mg concentration, pumped by shallow seepage reflux and/or evaporitic tidal pumping (Morrow, 1978;Saller & Yaremko, 1994;Zenger, 1996a;Baniak et al, 2014;Baldermann et al, 2015;Niu et al, 2020;Rahim et al, 2020;Alibrahim et al, 2021;Ye et al, 2021;Yang et al, 2022a). Moreover, Callen & Herrmann (2019) found that the leaching of volcanic ash could provide Mg for burrow dolomitization. Jones et al (1979) proposed that the upward migration of burial brine brought Mg ions, and Zenger (1996a) suggested that Mg was sourced from the overlaying evaporites in the burial realm.…”
Section: Introductionmentioning
confidence: 99%
“…Barite was observed under a microscope. Meanwhile, there was the obvious Eu positive anomaly of the two types of dolostone and the heavy rare earth elements were relatively enriched in the meso-coarse crystalline dolostones, indicating a strong reducing environment probably caused by the hydrothermal fluids [32,[58][59][60]. These characteristics indicate that the digenesis of the two types of dolostones were influenced by hydrothermal fluids.…”
Section: Dolomitization Of Dolostone Formed By Hydrothermal Fluidsmentioning
confidence: 95%
“…According to the Formulas (1) and ( 2) [27][28][29]32], the ancient seawater temperature of the Qixia period in the study area was calculated (Table 5). As shown in Table 5, the Ts of the Qixia period was between 11.35 and 25.87 • C, with an average value of 21.26 • C. At the same time, the oxygen isotope values could also be used to calculate the temperature of the precipitation of carbonate minerals (Tc) [33].…”
Section: C O Sr Isotopesmentioning
confidence: 99%
See 1 more Smart Citation